Involuntary displacement and resettlement to make way for diamond mining: the case of Chiadzwa villagers in Marange, Zimbabwe - Madebwe, Crescentia; Madebwe, Victor; Mavusa, Sophia (International Research Journals, 2016)
Rural communities bear a disproportionate burden of the cost of development projects. The paper is a preliminary examination of the displacement and resettlement in May 2011 of villagers from Chiadzwa in Marange communal area to make way for diamond mining. Data was collected using semistructured questionnaires and key informant interviews. Snowball sampling was used to recruit respondents. By December 2011, a total of 600 families will have been resettled at ARDA Transau farm in Odzi in Manicaland Province. More displacements from the mining concession are planned for 2012 and 2013 as determined by stages in mining development. To avert homelessness, landlessness and food insecurity each displaced family was allocated a 3-bedroomed house, 11hectares of arable land including 1 hectare earmarked for irrigation and a once off US$1 000 disturbance allowance. Each family will also get agricultural inputs for the first agriculture season post resettlement and basic food items every four months until the next harvest. Five months after relocation displaced families do not know how much and when they will get compensation for loss of economic and non economic assets. Two months before the start of the agriculture season land preparation has not started. Secondary school pupils travel 8 km to the nearest school. Pre- displacement the families’ derived livelihood from agriculture and artisanal diamond mining. Current initiatives foster dependency rather than rehabilitation, development and livelihood sustainability.